The moving finger - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Miss Marple mystery., 2022)
The placid village of Lymstock seems the perfect place for Jerry Burton to recuperate from his accident under the care of his sister, Joanna. But soon a series of vicious poison-pen letters destroys the village's quiet charm, eventually causing one recipient to commit suicide. The vicar, the doctor, the servants -- all are on the verge of accusing one another when help arrives from an unexpected quarter. The vicar's houseguest happens to be none other than Jane Marple.